Health Statistics The Australian Experience and Opportunities - Madden, Richard (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Health statistics have progressed dramatically in Australia since the 1980s when the Australian Government created the (now) Australian Institute of Health and Welfare. The 12 papers in this Special Issue describe developments across a diverse range of topics, as well as providing an overview of the scope of health statistics in Australia and describing some ongoing gaps and problems. The papers will be of interest to international readers seeking to improve statistics about their health systems. Health statistics need to respect individuals' personal information, be based on common data standards, and have adequate resourcing and committed staffing . The Australian experience provides valuable insights and examples. Australians will benefit from a comprehensive account of what has been achieved and what remains to be addressed. The papers in the Special Issue demonstrate the importance of continuing commitment to the statistical effort. Authors were chosen because of their known expertise in their respective fields.